On the Conditional Risk and Performance of Financially Distressed Stocks - O'Doherty, Michael S. (Management Science, 2012)
Several recent articles find that stocks with high probabilities of bankruptcy or default earn anomalously low returns and negative unconditional capital asset pricing model (CAPM) alphas in the post-1980 period. I show that the conditional CAPM resolves the performance difference between high- and low-distress stocks. In particular, financially distressed stocks have relatively low exposure to market risk during bad economic times. I help to explain these findings through a theoretical model in which a levered firm's equity beta is negatively related to uncertainty about the unobserved value of its underlying assets. This paper was accepted by Wei Xiong, finance.